Pengaruh Pemanfaatan Teknologi Informasi dan Komunikasi (TIK), Pelatihan Guru, dan Supervisi Guru terhadap Kinerja Guru di SMP XYZ Tangerang - Sitanggang, Elisa Marhamah (Jurnal Ketopong Pendidikan, 2023)
One of the main reasons for the decline in student enrollment is the quality of education, in which teachers play a vital role as a key factor in the success of the learning process at school. Teacher performance, as educators, must be continuously improved to ensure effective learning outcomes. Therefore, professional training is essential to enhance teachers’ competencies, particularly in utilizing information and communication technology (ICT) as a tool to support learning activities and access various sources of knowledge. This study aims to determine the influence of ICT utilization, teacher training, and teacher supervision on teacher performance at SMP XYZ Tangerang. The research uses a quantitative approach with regression analysis methods. Data analysis techniques include descriptive statistics, inferential statistics, and hypothesis testing. The population of this study consists of all teachers at SMP XYZ Tangerang. The findings reveal that: (1) the use of ICT has a positive and significant effect on teacher performance; (2) teacher training positively affects teacher performance; and (3) teacher supervision also contributes positively to improving teacher performance. These results indicate that continuous training, effective supervision, and the use of technology play an important role in enhancing the overall quality and professionalism of teachers.